The Effect of Financial Ratios on Firm Value in the Food and Beverage Sector of the IDX - Marsha, Nadya; Murtaqi, Isrochmani (Journal of Business and Management, 2017)
Abstract.This research examines the use of Financial Ratios (ROA, Current Ratio, and Acid Test Ratio) and its effect on Firm Value of 14 Indonesia Firms in the Food and Beverages sector for period of 2010-2014. Tobin Q Ratio is used as the measure for Firm Value to investigate whether Financial Ratios has effect on Firm Value or not. This is investigated by using multiple regression analysis with ROA, CR, and ATR as the independent variable and Firm Value as dependent variable. The result of this study is that all three financial ratios has significant effect to firm value. ROA and Current Ratio have a positive relationship with Firm Value, while Acid Test Ratio has a negative relationship. On the basis of these findings, the study concludes that companies need to pay more attention on financial ratios and that there is increasing need for a more credible and comprehensive disclosure of financial ratios in the annual reports of firms.Â Keywords: Financial ratios; Firm Value; Multiple Regression Analysis; Tobin Q Ratio